Analisis Faktor-Faktor yang Mempengaruhi Speech Delay pada Anak Usia Dini - Ananda, Adelya Zahra; Marsofiyati, Marsofiyati; Utari, Eka Dewi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
Speech delay in early childhood is increasingly common in the digital era. This study aims to analyze the factors that influence speech delay, with an emphasis on external factors such as excessive use of gadgets. The research method uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews with five parents who have children aged 1-6 years with symptoms of speech delay in the Jakarta and Depok areas, as well as literature studies. Data were analyzed using thematic analysis through the process of open coding, categorization, and identification of main themes. The results showed that the most dominant external factors were lack of verbal interaction in the family and excessive use of gadgets. Meanwhile, internal factors such as gender and history of premature birth also contributed. This study emphasizes the importance of the role of parents, teachers and health workers in providing verbal stimulation and detecting speech delay early to support children's optimal language development.